Law and anti-anthropocentric (and anti-humanist) trends in AI. A reflection (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Law, in relating to the diffusive proceeding of algorithmic ICTs, must pay special attention to certain tendencies that could be called anti-anthropocentric (sometimes even anti-humanistic). These tendencies, in fact, in referring to the human species or its individuals, contradict the fundamental values of our legal systems. The following are examples: the equalisation of human and artificial intelligence, the introduction of limiting factors to the development processes of human thought, the de-materialised patrimonialisation of the human being that increasingly becomes a reservoir of data and information for the benefit of the market, the informationalist reductionism of the concept of the person and a new and counterintuitive concept of power (algocracy and infocracy). Trends that require, to be effectively addressed, an interdisciplinary, global and intergenerational approach that places the human being at the foundation of the legal discipline.
Keywords: Anti-anthropocentrism; anti-humanism; AI; algorithms; rights